Up-regulation of pro-inflammatory genes as adaptation to hypoxia in MCF-7 cells and in human mammary invasive carcinoma microenvironment - Tafani, Marco; Russo, Andrea; Di Vito, Maura; Sale, Patrizio; Pellegrini, Laura; Schito, Luana; Gentileschi, Stefano; Bracaglia, Roberto; Marandino, Ferdinando; Garaci, Enrico; Russo, Matteo A (Cancer science, 2010)
The role of tumor cells in synthesizing pro‐inflammatory molecules is still controversial. Here we report that hypoxic treatment of the MCF‐7 human mammary adenocarcinoma cell line induced activation of hypoxia‐inducible factor 1α (HIF‐1α) and nuclear factor‐kappa B (NF‐κB). Importantly, hypoxia regulated expression of alarmin receptors such as the receptor for advanced glycation end products (RAGE) and the purinoreceptor (P2X7R), and up‐regulated inflammatory response (IR) genes such as the inducible enzymes nitric oxide synthase (NOS2), cycloxygenase (COX2), and the acute‐phase protein pentraxin‐3 (PTX3). Hypoxia also stimulated chemokine (C‐X‐C motif) receptor 4 (CXCR4) mRNA synthesis. In fact, the CXCR4 ligand stromal‐derived factor‐1α (SDF‐1α) increased invasion and migration of hypoxic MCF‐7 cells. Inhibition of HIF‐1α by chetomin and NF‐κB by parthenolide reduced mRNA and protein expression of the studied molecules and prevented invasion of hypoxic MCF‐7 cells. Moreover, solid invasive mammary tumor microenvironment was analyzed after laser‐capture microdissection (LCMD) comparing tumor versus host normal tissue. Nuclear translocation of HIF‐1α and NF‐κB and up‐regulation of IR, CXCR4, estrogen receptor α (ERα), and epithelial growth factor receptor (EGFR) was observed in tumor but not in host normal tissue in the absence of a local inflammatory leukocyte infiltrate. We conclude that under hypoxic conditions MCF‐7 cells acquire a pro‐inflammatory phenotype, and that solid human mammary carcinoma evidenced a similar activation of HIF‐1α, NF‐κB, and IR genes in malignant tumor cells as compared to the normal host tissues. We suggest a role for IR activation in the malignant progression of transformed cells. (Cancer Sci 2010; 101: 1014–1023)